Strengthening The Product Development of Straw Mushroom To Enhance The Welfare And Sustainable Development Goals In Wonokerso, Malang - Suwanan, Ahmad Fawaiq; Rahmat, Andro Agil Nur; Kurniawan, Dediek; Firmansyah, Rizky; Nuraini, Fariha; Lupita, Delia (International Journal Of Community Service, 2023)
Sustainable development is a common goal of countries in the world, including Indonesia. In the process of its realization, sustainable development Goals or SDGs have an impact on various aspects of life, including overcoming food security problems. To achieve the SDGs, the participation of many parties is necessary. The form of community participation can be achieved by conducting training or counseling activities in the product development of local potential commodities, one of which is the mushrooms. Paddy straw mushroom is one type of mushroom that has a high protein content and is low in calories. Through capacity building in Wonokerso Village, Pakisaji, Malang Regency, we expect to be able to increase participants' skills and insights about the straw mushrooms product development in order to develop jobs in achieving sustainable development goals. Participants not only strengthen their mushroom product development skills but also increase their knowledge in preparing the media for cultivation. Participants were very enthusiastic because the theme conveyed in the activity was very relevant, it is hoped that with this activity participants can increase the ability and understanding of the community to cultivate straw mushrooms to be sold in various urban areas through business partners. In the activities that have been carried out, the final assessment results of training showed high knowledge about the cultivation of straw mushrooms compared to the results of initial knowledge and obtained sustainability analysis to provide advanced training in the cultivation of paddy straw mushrooms in the post-harvest process.